2018
DOI: 10.1155/2018/7826576
|View full text |Cite
|
Sign up to set email alerts
|

Manilkara zapota (L.) P. Royen Leaf Water Extract Induces Apoptosis in Human Hepatocellular Carcinoma (HepG2) Cells via ERK1/2/Akt1/JNK1 Signaling Pathways

Abstract: Manilkara zapota (L.) P. Royen, called sapodilla, or locally known as ciku, belongs to the family Sapotaceae. We found that Manilkara zapota leaf water extract has cytotoxic effect against human hepatocellular carcinoma (HepG2) cell line in our earlier study. Therefore, this study aimed to explore the anticancer properties of Manilkara zapota leaf water extract in HepG2 cells. We also aimed to unravel yet undiscovered mechanisms and identified several expressed genes whose functions in cytotoxicity activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Phytochemicals, with natural plants being their potential sources and which include flavonoids, polyphenols, terpenoids, alkaloids, saponins, coumarins and so on, could target diverse signaling pathways, which may be a favorable way to block cancer progression and chemotherapy drug resistance. 15–38…”
Section: Phytochemicals For Cancer Prevention and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemicals, with natural plants being their potential sources and which include flavonoids, polyphenols, terpenoids, alkaloids, saponins, coumarins and so on, could target diverse signaling pathways, which may be a favorable way to block cancer progression and chemotherapy drug resistance. 15–38…”
Section: Phytochemicals For Cancer Prevention and Therapymentioning
confidence: 99%
“…34 Manilkara zapota (L.) P. Royen belongs to the sapotaceae family. Manilkara zapota leaf water extracts, which can induce the formation of ROS, upregulate the expression of JNK1 and inducible nitric oxide synthase (iNOS), and reduce the levels of AKT and vascular endothelial growth factor A (VEGFA) to induce HepG2 cell apoptosis; 35 they also suppress NF-κB and EGFR transcriptional activity to enhance apoptosis of heLa human cervical cancer cells. 36 2- O -Methylmagnolol, a derivative of magnolol bearing one methoxy moiety, increases lncRNA growth arrest-specific 5 (GAS5) expression to induce skin cancer cell apoptosis.…”
Section: Phytochemicals For Cancer Prevention and Therapymentioning
confidence: 99%
“…Higher concentrations inhibited the growth of liver cancer cells. Tan et al (2018) showed that the percentage of viable cells was significantly inhibited in samples at higher concentrations (25-200 µg/mL) compared to the control group. The samples were tested for glucose uptake into HepG2 cells.…”
Section: Cell Culturementioning
confidence: 93%
“…This study revealed that leaf water extract causes early apoptosis in hepatocellular carcinoma (HepG2 cells) via modulation of multiple signalling pathways like intrinsic mitochondrial pathways leads suppression of metastasis. All the data recorded indicated that M. zapota leaf water extract has noteworthy apoptotic potentials via the regulation of ERK1/2/Akt1/JNK1 transcriptional activity [38] . The ethyl acetate extract of stem bark of M. zapota showed significant antitumour efficacy in Ehrlich ascites carcinoma model.…”
Section: Anticancer Activitymentioning
confidence: 94%